Association of postpartum depression and epidural analgesia in women during labor: an observational study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2021)
Background and objectives: Postpartum depression affects women, manifesting with depressed mood, insomnia, psychomotor retardation, and suicidal thoughts. Our study examined if there is an association between epidural analgesia use and postpartum depression. Methods: Patients were divided into two groups. One group received epidural analgesia during labor while the second group did not. The Edinburgh postnatal depression scale (EPDS) was administered to patients prior to birth and 6 weeks postpartum. Pain severity was assessed by the Visual Analogue Scale (VAS) during labor and at 24 hours postpartum. Results: Of the 92 patients analyzed, 47.8% (n = 44) received epidural analgesia. We detected significantly higher VAS score during labor (p = 0.007) and 24 hours postpartum (p = 0.0001) in the group without epidural analgesia. At 6 weeks postpartum, a significant difference was observed between the EPDS scores of both groups (p = 0.0001). Regression analysis revealed higher depression scores in patients experiencing higher levels of pain during labor (OR = 0.572, p = 0.039). Epidural analgesia strongly correlated with lower scores of depression (OR = 0.29, p = 0.0001). Conclusion: The group that received epidural analgesia had lower pain scores. A high correlation between epidural analgesia and lower depression levels was found. Pregnant women giving birth via the vaginal route and having high pain scores could reduce postnatal depression scores using epidural labor analgesia. Pregnant women should opt for epidural analgesia during labor to lessen postpartum depression levels. (c) 2021 Published by Elsevier Editora Ltda. on behalf of Sociedade Brasileira de Anestesiologia. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/ licenses/by-nc-nd/4.0/).
Keywords: Postpartum depression; Edinburgh postnatal depression scale; Epidural analgesia; Visual Analogue Scale; Vaginal birth; CONTROLLED INTRAVENOUS ANALGESIA; HEALTH-PROBLEMS; PAIN; CHILDBIRTH; DELIVERY; ANXIETY; SCALE; RISK